(untitled) (Medico Legal Update, 2021)
Self medication is considered as key aspect of primary health care to treat minor symptoms. However, inappropriate practice of self medication and related potential dangers has become public health concern worldwide. Objectives: This study aimed at assessing the prevalence and frequency of practicing self medication. Common self diagnosed Disorders and prime reasons for engaging in self medication were explored by the researchers. Also, association between self medication and various sociodemographic variables was also discovered. Method: The study employed exploratory design. A self structured questionnaire was administered to 500 students of selected University. The data were summarized and analyzed using descriptive and inferential statistics. Results: Overall 442 (88.4%) students practiced self medication and approximately 77% of study subjects consume self medications occasionally. Headache (84.4%), common cold (83.8%), cough (82.6%) and gastric acidity (81.8%) were the most common minor ailments for which self medication is being taken. Major driving factors behind self medication are considering minor ailments non- seriously (83%), easy availability of medicines (82%) and lack of trust in institute dispensaries (79%). Further, no significant association was found between self medication practices and age, gender, year of study, academic disciplines, parents’ education level, place of residence. Conclusion: Prevalence of self medication is remarkably high among scholars which constitutes health concern that requires conduction of awareness programs on risk and benefit of self medication at university level and stringent laws on sale of medicines without current prescription needs to be enforced to control malpractice.